The System of Educational Needs of National Minorities in Education in Ukraine - TULIN, Kyrylo (Journal of Research in Educational Sciences; Vol 13 No 15 (2022): JRES, Volume XIII, Issue 15, Winter 2022DO - 10.14505/jres.v13.15.04, 2022)
The authors analyze the current system of educational needs of national minorities in Ukraine by defining the system of education, including legal policy, institutional and organizational guarantees, identifying problematic aspects in the sphere of Ukrainian education and identifying opportunities to overcome them, analyzing the status of educational needs of national minorities. It is indicated that global transformations have intensified the tendencies of the number of national minorities due to global demographic processes, including migration and refugees. It is argued that the elements of the system of educational needs of national minorities in education in Ukraine are international, European regional, and national legal acts, the functioning of public authorities, the complex structure of educational institutions at all levels, and additional organizational and economic guarantees of educational rights. International, regional, and national legal norms are analyzed. Positive aspects and shortcomings of the legal regulation of the educational sphere of national minorities are indicated. A number of improvements to the current ethnopolitics of Ukraine in the context of the implementation of international and European standards and the positive practice of democratic states, including Romania, are proposed. The methodological basis of the study is a system of philosophical, general scientific, and specifically scientific methods. The sociological survey, conducted on the author's questionnaire, represents the real state of national minorities education in Ukraine. The Russian, Hungarian, Slovak, and Polish national minorities are taken into account. The authors proved that the pandemic crisis has a particularly negative effect on the education of national minorities.